AB1163 Prevalence of Smoking and Impact on Disease Parameters Among Ankylosing Spondylitis, Rheumatoid Arthritis and Psoriatic Arthritis Patients Treated with Infliximab or Golimumab. (9th June 2015) - Faraawi, R.; Dixit, S.; Mulgund, M.; Bensen, W.; Kelsall, J.; Choquette, D.; Baker, M.; Fortin, I.; Sampalis, J.; Rampakakis, E.; Tkaczyk, C.; Lehman, A.; et al.
Abstract : Background: Smoking can compromise the response to biologic treatment in rheumatoid arthritis (RA) patients. Objectives: The aim of this analysis was to compare patient characteristics and baseline disease parameters based on smoking status at initiation of anti-TNF treatment and to assess the impact of smoking on anti-TNF effectiveness in RA, ankylosing spondylitis (AS), and psoriatic arthritis (PsA) patients treated with infliximab (IFX) or golimumab (GLM). Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with IFX or GLM. The analysis was based on patients with available smoking status treated with IFX or GLM between 2010-2014. Between-group differences were assessed for statistical significance with the independent-samples t-test or Chi-square test. Results: Among the 478 patients included in the analysis, there were 143 (29.9%) AS, 237 (49.6%) RA, and 98 (20.5%) PsA patients. At baseline, the proportion of current smokers was 27.3% in AS, 19.8% in RA, and 19.4% in PsA (P=0.186). Overall, no significant differences in baseline characteristics were observed based on smoking status except for gender among AS patients and TJC28 which was higher among smoking PsA patients. Upon 6 months of treatment, statistically significant and clinically meaningful improvements in almost all parameters were observed, regardless of smoking status and diagnosis. Although statistical significance was not achieved, a greater proportion of non-smokers achieved CDAI LDA (RA: 49.0% vs. 34.8%, P=0.252; PsA: 68.3% vs. 50.0%, P=0.296), SDAI LDA (RA: 56.7% vs. 33.3%, P=0.152; PsA: 69.0% vs. 57.1%, P=0.664) and DAS28 LDA (RA: 50.0% vs. 38.1%, P=0.458; PsA: 59.4% vs. 37.5%, P=0.430) at 6 months. After 6 months of treatment, no significant between-group differences were observed in the improvement of disease parameters in all diagnoses with the exception of PtGA in RA patients which was greater among non-smokers (-21.8 vs. -6.2, P=0.047), and ESR (-21.2 vs. -6.4, P=0.006) and CRP (-19.8 vs. -7.9, P=0.052) levels in AS patients which were greater among smokers. Conclusions: The results showed that the rate of smoking among Canadian RA and PsA patients treated with anti-TNF is comparable to the general population. Smoking rates among AS patients, however, were greater. Numerical, although not statistically significant, differences were observed in the response to 6 months treatment based on smoking status. Regardless of smoking status, treatment with IFX or GLM was effective in improving disease severity outcomes and reducing symptom severity among AS, RA or PsA patients. Disclosure of Interest: R. Faraawi Consultant for: Janssen, S. Dixit: None declared, M. Mulgund: None declared, W. Bensen Consultant for: Janssen, J. Kelsall Consultant for: Janssen, D. Choquette Consultant for: AbbVie, Amgen, Celgene, BMS Canada, Janssen, Pfizer, M. Baker: None declared, I. Fortin Consultant for: Janssen, J. Sampalis Shareholder of: JSS Medical Research, Employee of: JSS Medical Research, E. Rampakakis Employee of: JSS Medical Research, C. Tkaczyk Employee of: Janssen, A. Lehman Employee of: Janssen, F. Nantel Employee of: Janssen